THE DOMINANT FACTOR FOR IMPROVING INFORMATION SECURITY AWARENESS - Iffah Budiningsih; Tjiptogoro Dinarjo Soehari; Irwansyah Irwansyah (Jurnal Cakrawala Pendidikan, 2019)
The advancement of science and technology especially in the field of Information Communication Technology (ICT) is characterized by the availability of information access faster, easier, convenient, but also vulnerable to try to steal (tap) and modify information. This study aims to determine the relationship between organizational support perception, competence, and motivation with information security awareness. The survey involved a population of 324 people affordable employees in local government that handling information systems in 33 provinces. The sample was taken 140 people by stratified proportional random sampling. The data were collected using a questionnaire and analyzed using multiple regression. The results of the research show: (1) Information security awareness is influenced positively and significantly by the organizational support perception, competence and motivation, (2) The competence is the dominant factor that influences the information security awareness compared to the organizational support perception  and motivation, (3) Information security awareness can improve by competencies of knowledge, skill, attitude continuously and tiered, and  the model instructional awareness training developed by ‘Schultz’ can be used to improve the attitude or character of  information security awareness.